Prostatic cyst: An unusual cause of hemospermia - Hernández Galván, Fernando; Jaime Dávila, Rodolfo; Gómez Guerra, Lauro Salvador; Gutiérrez González, Adrián; Lozano Salinas, Juan Fermín; Arrambide Gutiérrez, José Gustavo (UANL. Facultad de Medicina, 2015)
A 31-year-old man was referred to our service because of recurrent hemospermia over the last 4 years, there were no other symptoms like perineal pain, fever, dysuria, nocturia or urgency; this patient only presented hemospermia with clots. Genital examination was normal. Semen analysis showed no change in volume and pH; however, hemospermia and asthenozoospermia were observed. The semen culture was normal. Ultrasonography only revealed the presence of a cystic lesion adjoining the prostate gland, next to the bladder neck. The retrograde urethrogram was normal. The CT scan revealed only a small calcification in the right seminal vesicle. Endoscopic cistourethroscopy demonstrated 2 cystic dilatations arising on both sides of the prostate gland adjacent to the bladder neck, behind the verumontanum with vessels running over the surface prostatic cyst dilatation. The diagnosis of prostatic gland cystic dilatation was reached and confirmed by pathology that reported fibroconnective tissue with fibrosis and hyalinization. Transurethral unroofing of the cyst was performed separately with a successful outcome.